Charcoal Hemoperfusion for Methotrexate Toxicity: A Safe and Effective Life-Rescue Alternative When Glucarpidase Is Not Available - Rosales, Alejandra; Madrid, Alvaro; Muñoz, Marina; Dapena, Jose Luis; Ariceta, Gema (Frontiers in Pediatrics, 2021)
Background: High dose methotrexate (HDMTX) is used for the treatment of pediatric hemato-oncological diseases. HDMTX can induce acute kidney injury in cases of delayed elimination. The use of leucovorin remains the most effective rescue action. Further treatment options are of difficult access in the rare cases where leucovorin fails to prevent renal failure from ocurring. Glucarpidase is an effective treatment in cases of methotrexate (MTX) delayed elimination, but cost is high and availability is limited. Charcoal hemoperfusion (CHP) is a very efficient procedure to remove protein-bound drugs, promoting fast MTX elimination, but is rarely considered as a treatment option. Methods: We present three pediatric cases with prolonged exposure to MTX after HDMTX and delayed elimination in which hemoperfusion was performed as rescue treatment for methotrexate intoxication. Results: Charcoal hemoperfusion was performed with positive results and no complications as bridging until glucarpidase was available in two cases and in one case where two doses of glucarpidase led to insufficient reduction of MTX levels. Conclusions: CHP can be considered as a rescue treatment option in MTX intoxication, since it is an effective and safe extracorporeal method for removing MTX, in cases where rescue with leucovorin is insufficient and glucarpidase is not available or while waiting for delivery.